Economic analysis of phase change material integrated photovoltaic thermal systems : A short communication - Jacob, Jeeja; Paul Nadakkal, John; Selvaraj, Jeyraj; Kadirgama, Kumaran (Institute of Physics, 2023)
Solar energy is the most prospective renewable resource that humankind has access to, for acquiring the most usable energy. Photovoltaic thermal systems (PVT) are deemed to be one among the most efficient methods for capturing solar energy because of their distinct ability to produce electrical power by photovoltaic conversion while simultaneously dissipating the heat generated in the process. The necessity of financial investment is a major stumbling block in putting this strategy into action in actual application. This paper delivers updated literature on the economic aspects of PVT-Phase change materials (PCM) systems (installation, operation, and maintenance) that several researchers had carried out. Payback time is taken into account while calculating the profitability of PVT systems. Finally, the performances of several PVT-PCM systems were compared, and the economic analysis confirmed that the PVT system is financially viable. PVT system holds tremendous potential to be incorporated in residential/commercial buildings. The PVT system is a promising technology that still needs refinement in terms of overall efficiency and environmental factors, according to the available literature assessments.